Madagascar Economic Update, October 2019 : A New Start? - World Bank (Washington, DC: World Bank, 2019)
The successful conclusion of the Presidential election in January 2019 represents a historic window of opportunity for Madagascar to break cycles of political instability that abruptly interrupted its development in the past and to leapfrog its economic and social revitalization. Following a prolonged period of economic stagnation, growth accelerated over the last five years to reach 5.1 percent in 2018, its fastest pace in over a decade. The return to constitutional order in 2014 was instrumental to this economic revival, as it contributed to restore investor confidence, re-open access to key export markets, reinstate flows of concessional financing, and encourage structural reforms. Growth continued apace in 2019, although moderating slightly to an estimated 4.7 percent, amid weakening external demand and a slow execution of public spending following the presidential and parliamentary elections. A post-election rebound in public and private investments is expected to result in growth averaging 5.4 percent in 2020-21. This Economic Update suggests however that the country remains vulnerable to shocks. International risks include the possible intensification of the trade war between main trading partners, or the rise in international oil prices in a context of geopolitical tensions. The risk of natural disasters or of a sharp drop in the price of vanilla also need due consideration. The government must take advantage of the successful political transition to accelerate growth-enhancing reforms and develop the necessary fiscal buffers to support priority investments and be ready to face unexpected circumstances.